Psychometric properties of the Exercise Benefits/Barriers Scale in Mexican elderly women - Enríquez Reyna, María Cristina; Cruz Castruita, Rosa María; Ceballos Gurrola, Oswaldo; Garcia Cadena, Cirilo Humberto; Hernández Cortés, Perla Lizeth; Guevara Valtier, Milton Carlos (2017)
Objective: analyze and assess the psychometric properties of the subscales in the Spanish version of the Exercise Benefits/Barriers Scale in an elderly population in the Northeast of Mexico. Method: methodological study. The sample consisted of 329 elderly associated with one of the five public centers for senior citizens in the metropolitan area of Northeast Mexico. The psychometric properties included the assessment of the Cronbach’s alpha coefficient, the Kaiser Meyer Olkin coefficient, the inter-item correlation, exploratory and confirmatory factor analysis. Results: in the principal components analysis, two components were identified based on the 43 items in the scale. The item-total correlation coefficient of the exercise benefits subscale was good. Nevertheless, the coefficient for the exercise barriers subscale revealed inconsistencies. The reliability and validity were acceptable. The confirmatory factor analysis revealed that the elimination of items improved the goodness of fit of the baseline scale, without affecting its validity or reliability. Conclusion: the Exercise Benefits/Barriers subscale presented satisfactory psychometric properties for the Mexican context. A 15-item short version is presented with factorial structure, validity and reliability similar to the complete scale. Descriptors: Psychometrics; Exercise; Nursing; Perception; Validation Studies